E. H. WOLGAST’S CRITIQUE OF INDIVIDUALISM AS SOCIAL ATOMISM - Dağ, Umut (My University, 2022)
Individualism is an important philosophical idea that determines and shapes the modern political philosophy, and especially liberalism as a political theory. In the context of political thought, individualism gives priority to the individual over society and state. This priority results in the idea that each individual has inviolable rights and these rights must be protected by laws. The aim of this paper was to illuminate Wolgast’s critique of individualism. Wolgast gave a systematic critique of individualism in her work. Her critique was based on the conception of social atomism. Before analyzing her critique, in Section 1, the basic definition and explanation of individualism will briefly be given. Then, this concept will be elucidated in the realm of political philosophy. In Section 2, the conception of social atomism will be explicated. According to Wolgast, social atomism justifies and characterizes individualism as a political thought. In Section 3, Wolgast’s critique of individualism will be explicated in the context of social atomism. In doing so, focus will be placed on her critique of individual rights, which is at the center of individualism as political thought for her. Section 4 presents an evaluation and critique of Wolgast’ s ideas on individualism.